Effect of Molecular Weight of Chitosan in The Coating Solutions on The Shelf Life of Tuna Fish Fillets - Indarti, Dwi; Khofifah, Marhamatul; Piluharto, Bambang; Ananda, Tinok Dwi (al Kimiya: Jurnal Ilmu Kimia dan Terapan, 2025)
Tuna, a valuable Indonesian marine commodity, is known for its highly valued dietary and nutritional sources. However, this red meat fish is particularly prone to deterioration and spoilage due to its inherent properties. Liquid smoking, a popular fish preservation method in Indonesia, has garnered significant consumer interest but remains insufficient to prevent fish decay entirely. Therefore, this study aimed to enhance tuna fish fillet (TFF) shelf life by developing a novel coating solution. This solution contains liquid smoke seasoning and chitosan with varying molecular weights (MW), as this property affects chitosan’s chemical, physical, and biological characteristics. In this research, fresh tuna were divided into four groups: a control group with no coating, a group with liquid smoke coating only (LS), a group coated using chitosan solution (Ch) with variations of MW (Low: 50-190 kDa, Medium: 190-310 kDa, and High: 210-375 kDa), and a group coated using liquid smoke seasoning with the same chitosan MW variation (Ch + LS). During 15 days of storage in the freezer, their chemical properties (pH, and Total Volatile Base Nitrogen - TVB-N) were analyzed. The finding showed that combining high MW of chitosan and liquid smoke as a coating solution improved TFF appearance, maintaining a desirable uniformly cherry red color. Moreover, this treatment showed a slower increase in pH (5.5 – 5.7) and TVB-N level (22 – 28 mg TVB-N/100 gram), indicating deterioration and spoilage delay during 15 days of storage compared to other treatments. This study underscores the efficacy of a preservation strategy in inhibiting deterioration and spoilage in tuna fish fillets during storage, thereby enhancing product quality and ensuring consumer safety.